THE BASIC REGULATOR OF THE CIRCADIAN SYSTEM IN EPILEPSY - G. N. Avakyan; O. M. Oleinikova; E. N. Kareva; M. A. Bogomazova (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: there were significant increase in the values of the evening melatonin excretion in the spring of the year compared to the autumn. In patients with epilepsy, nocturnal seizures, nocturnal melatonin excretion two times lower than in patients with daytime seizures. In the spring, the evening excretion increased COMT 6; concentration morning urinary 6-COMT higher with anticonvulsant therapy with valproic acid compared with carbamazepine.